Letter (copy) : Spanish situation - Citrine, Walter, 1887-1983
010-0017-001 WMC/FEM/MT/364 Secretary's 4th January, 1937. Mr. W. Schevenels, International Federation of Trade Unions, 9, Avenue D'Orsay, PARIS, VIIe, FRANCE. Dear Mr. Schevenels, Spanish Situation. Thank you for your letter of the 28th December, urging all National Trade Union organisations to do their utmost in boycotting any transport of whatever goods there may be despatched or suspected to be despatched to the Spanish rebels, and suggesting for this purpose the creation of a small permanent Supervisory Committee. In this country, as you are aware, the British Government has already placed an embargo on the supply of war materials to Spain. This applies also to the carrying of war materials in British ships. We are not aware of any goods that are being despatched to the rebels in Spain from this country. In any case, the National Council of Labour is as you know, the national co-ordinating body for the whole Labour Movement in this country, and they are constantly reviewing the position. You can rest assured that if any such cases come to their notice, they will take whatever steps are possible to deal with the matter. Yours fraternally, General Secretary. 292/946/10/17